From Da’wah to Spectacle: Negotiating Sacred Space and Ritual Meaning in The Commodification of Sekaten - Mukhlis Anton Nugroho; Bambang Sunarto; Budi Setiyono (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2025)
Abstract: This study examines how the Sekaten ritual in Surakarta has shifted from an Islamic da’wah-centred ceremony into a commodified cultural festival shaped by mass tourism and urban entertainment. Using a qualitative socio-cultural design grounded in cultural ethnography, the research draws on participatory observation conducted during the 2023–2025 celebrations at the alun-alun (town square), the Grand Mosque, the night market, and Bangsal Pagongan (theatre ward), alongside purposive interviews with abdi dalem (palace retainers), mosque administrators, vendors, and festival attendees. The analysis applies cultural transformation theory (Nasukah & Winarti, 2021), Lefebvre’s theory of the social production of space (Lefebvre, 1991), and ritual commodification theory (D. Picard & Robinson, 2006) to trace how shifts in actors, spatial organisation, and symbolic interpretation reorient the ritual’s meanings. Findings indicate that municipal institutions and market stakeholders are increasingly governing Sekaten through the dominance of the night market, commercial stages, and sponsorships, while traditional custodianship by the Kraton (palace) and Masjid Agung is becoming more marginal. Sacred elements, such as the Gamelan Sekaten (traditional music), Miyos Gangsa (ritual procession), and ritual symbols including nginang (chewing betel nut) and janur (decorated palm leaves), persist; yet, they often operate as aesthetic markers within a spectacle economy rather than as central media of religious pedagogy. This reconfiguration produces spatial secularisation as the alun-alun transitions from a sacred zone into a consumerist arena, and public participation shifts from spiritual aspiration towards leisure-oriented consumption, particularly among younger visitors. This study advances debates on religion, space, and heritage governance by demonstrating that ritual changes in contemporary Java reflect negotiated struggles over symbolic power—rather than mere cultural decline. It advocates for participatory preservation strategies that sustain both ritual meaning and physical form amid tourism-driven urban development.